Determinants of Financial Management Behavior Based on Financial Literacy, Social Influence, and Financial Technology Usage Among Generation Z in Surabaya - Haura Rizqi Dzakiyyah Chandra; Jojok Dwiridotjahjono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Amid the rapid digitalization of Surabaya’s economy, Generation Z faces significant challenges in managing their personal finances. This study aims to analyze the influence of Financial Literacy, Social Influence, and Financial Technology Usage on Financial Management Behavior among Generation Z in Surabaya. A quantitative approach was used in this study, employing a non-probability sampling technique by distributing questionnaires to 175 Generation Z respondents in Surabaya, which were then analyzed using multiple linear regression. The results indicate that, both simultaneously and partially, Financial Literacy, Social Influence, and Financial Technology Usage have a positive and significant effect on Financial Management Behavior. These findings highlight the importance of strengthening financial literacy and fostering a supportive social environment to optimize the use of financial technology among young generation.